2001
DOI: 10.1152/ajpregu.2001.281.3.r960
|View full text |Cite
|
Sign up to set email alerts
|

Programming effects in sheep of prenatal growth restriction and glucocorticoid exposure

Abstract: Our aim was to determine the postnatal effects of single and repeated glucocorticoid injections during late gestation. Repeated (104, 111, 118, 125 days) or single (104 days) injections of betamethasone or saline were given to the ewe or by ultrasound guided injection to the fetus (term 150 days). Lambs were born spontaneously and studied at 3 and 6 mo and 1 yr of age. Arterial pressure was measured at each age, and we performed intravenous glucose tolerance tests at 6 mo and 1 yr. Repeated maternal, but not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
166
6
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(190 citation statements)
references
References 26 publications
17
166
6
1
Order By: Relevance
“…We have also shown that maternal betamethasone administration resulted in significantly elevated cortisol responses to a corticotrophinreleasing hormone+vasopressin challenge in offspring at 1 year of postnatal age (Sloboda et al 2002). These same animals exhibited significantly elevated postnatal insulin responses to a glucose load at 6 months and 1 year of age, as well as significantly higher basal glucose and glucose responses at 1 year of postnatal age (Moss et al 2001). It is not known whether hepatic function in these offspring was altered, although it is possible that alterations in hepatic gluconeogenesis may contribute to these effects.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…We have also shown that maternal betamethasone administration resulted in significantly elevated cortisol responses to a corticotrophinreleasing hormone+vasopressin challenge in offspring at 1 year of postnatal age (Sloboda et al 2002). These same animals exhibited significantly elevated postnatal insulin responses to a glucose load at 6 months and 1 year of age, as well as significantly higher basal glucose and glucose responses at 1 year of postnatal age (Moss et al 2001). It is not known whether hepatic function in these offspring was altered, although it is possible that alterations in hepatic gluconeogenesis may contribute to these effects.…”
Section: Introductionsupporting
confidence: 51%
“…It is possible that betamethasone treatment prematurely developed sympathetic suppression of insulin secretion, since previous studies have shown that glucocorticoids have a maturational effect on the sympathetic response at birth (Segar et al 1998(Segar et al , 2001(Segar et al , 2002. We have previously shown, however, that offspring treated with prenatal glucocorticoids exhibit exaggerated insulin responses to a glucose bolus at 1 year of postnatal age, rather than inhibited insulin secretion (Moss et al 2001). Furthermore, since cord insulin levels were not different at 146 days of gestation, any possible effect on the sympathetic regulation of insulin secretion due to betamethasone treatment in this study must have been transient.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Numerous reviews have concluded that there are no adverse consequences of a single course of glucocorticoid treatment on the preterm infant (NIH Consensus Conference 1995, Roberts & Dalziel 2006), but no published studies of which we are aware have investigated possible effects on maternal lactation. We previously observed a high rate of neonatal mortality after repeated treatment of pregnant sheep with betamethasone and subsequent delivery at term, which was attributed to a reduction in milk production (Moss et al 2001).…”
Section: Introductionmentioning
confidence: 99%